2020
DOI: 10.1101/2020.06.11.146605
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biased agonists of the chemokine receptor CXCR3 differentially drive formation of Gαi:β-arrestin complexes

Abstract: G-protein-coupled receptors (GPCRs), the largest family of cell surface receptors, signal through the proximal effectors G proteins and β-arrestins to influence nearly every biological process. Classically, the G protein and β-arrestin signaling pathways have largely been considered separable. Recently, direct interactions between Gα protein and β-arrestin have been described and suggest a distinct GPCR signaling pathway. Within these newly described Gα:β-arrestin complexes, Gαi/o, but not other Gα protein sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…While the formation of Gai:b-arrestin complexes was consistent across GPCRs, the Gai:b-arrestin complexes did not form the same ERK scaffolding functions downstream of all GPCRs, even within a homogenous cellular background. For example, downstream of CXCR3 Gai:b-arrestin: ERK complexes was not observed [92]. These data suggest that multiple other factors influencing Gai, b-arrestin, biased agonists, cellular context, and/or post-translational modifications (e.g., phosphorylation 'barcode') dictate scaffold formation.…”
Section: Gai:b-arrestin Complexes and Erk Signalingmentioning
confidence: 87%
“…While the formation of Gai:b-arrestin complexes was consistent across GPCRs, the Gai:b-arrestin complexes did not form the same ERK scaffolding functions downstream of all GPCRs, even within a homogenous cellular background. For example, downstream of CXCR3 Gai:b-arrestin: ERK complexes was not observed [92]. These data suggest that multiple other factors influencing Gai, b-arrestin, biased agonists, cellular context, and/or post-translational modifications (e.g., phosphorylation 'barcode') dictate scaffold formation.…”
Section: Gai:b-arrestin Complexes and Erk Signalingmentioning
confidence: 87%
“…CXCR3 is a chemokine receptor with three known endogenous ligands that exhibit biased signaling in various forms, such as in their differential formation of G i:β-arrestin complexes and markedly different abilities to induce G protein-or β-arrestin-mediated signaling [43][44][45][46] . We first determined if activation of CXCR3 using biased ligands promotes distinct patterns of GRK recruitment to the plasma membrane in HEK293 cells.…”
Section: Biased Ligands Demonstrate Different Grk Recruitment Pattern...mentioning
confidence: 99%
“…This demonstrated that the formation of a supercomplex of receptor, G protein, and arr critically depends on the conformation arr adapts upon binding to specific C termini. Most recently, a complementation assay leading to BRET in tripartite arr-receptor-G protein supercomplexes [110] has been proposed.…”
Section: Reporters Of Arrestin Recruitment and Intermolecular Interacmentioning
confidence: 99%